Strategi Pengembangan Badan Usaha Milik Desa Tirta Mandiri Ponggok Desa Ponggok Kabupaten Klaten Jawa Tengah - Danaresa, Wahyu; -, Turtiantoro; Herawati, Nunik Retno (Journal of Politic and Government Studies, 2018)
Development Strategy of Ponggok Tirta Mandiri Village Owned Enterprise Village of Ponggok Regency of Klaten, Central Java Province Abstract                  This study aims to find out how the strategy taken by the Tirta Mandiri Village Owned Enterprises, Ponggok Village, Klaten Regency, Central Java in managing the assets of village wealth so as to make the village income source to improve the welfare of the people of Ponggok Village. BUMDes Tirta Mandiri awarded by Kemendesa PDTT as Trendy Village because it can develop potential assets of the village in accordance with the present style in the era of social media that can attract tourists.                This descriptive study was conducted at the office of BUMDES Tirta Mandiri and office Kemendesa PDTT Kalibata with purposive sampling technique with primary data in the form of interview with the specified sample and secondary data obtained from various sources. Referring to the Master Strategy by Dan Schendel and Charles Hofer Higgins (in Salusu, 2005: 101) and the flow of organizational development systems according to Karl Albrecht (1985) which is poured into the major stages of organizational development according to McGill (1982: 156-157) .                The result of this research is that there are several factors supporting the establishment of BUMDes Tirta Mandiri, among which there are 3 springs of water source that become asset of village, supporting physical infrastructure, positive support from village community, BUMDes cooperation with PT. BNI46 (Persero), tbk, well-educated and professional management. The development of BUMDes Tirta Mandiri organization is based on social, kinship, and professional that become the main key in organizational development in BUMDES Tirta Mandiri.  Keywords: Organization Development, Village Owned Enterprise